The Role of Aqueous Garlic Extract (Allium Sativum) on Interleukin 10 and 12 in Leishmania Infected Macrophages - M Nobakht; F Fani; M.J Gharavi; M Bakhshayesh; Sh Khadem Vatan (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2011)
Background and Objectives: Leishmaniasis is a disease produced by several species of protozoa of the Leishmania genus. As a therapeutic agent, garlic (Allium sativum) is one of the most popular plants in traditional medicinal systems and is increasingly becoming important in herbal alternative therapy. The aim of the present study was to investigate the effects of aqueous garlic extract (AGE) on enhancing T-helper IL-10 and IL-12 cytokines in the culture via macrophages for engulfment and destruction of Leishmania.